Assessing the Role of Sharia-Compliant Investments in Promoting Clean Energy and Sustainable Economic Development: A Study of Asia’s Financial and Renewable Energy Sectors - Avazkhodjaev, Salokhiddin; Askarova, Mavluda; Achilova, Nargiza; Jalolova, Madina; Amirdjanova, Sitora; Otajonova, Charoskhon (International Journal of Energy Economics and Policy, 2024)
This study investigates the asymmetric impact of the Islamic stock market on clean energy prices and green economic development in the Asia-Pacific region using daily data from January 01, 2022, to May 31, 2024. Employing the Non-linear Autoregressive Distributed Lag (NARDL) model, we examined both long-term and short-term relationships between these variables. Our findings reveal significant cointegration, indicating a stable long- term relationship. In the long term, Islamic stock prices positively influence the clean energy market and green economic development, suggesting that Islamic finance can effectively support sustainable initiatives and environmental goals in the region. However, minor negative variations were observed, with an insignificant negative effect on green economic development over extended periods. In the short term, Islamic stock prices also demonstrate a significant positive effect on clean energy and green economic growth, highlighting their role in fostering immediate advancements in sustainable economic activities. Despite this, there are minor negative impacts, indicating that fluctuations in Islamic stock prices may occasionally result in short-term setbacks for clean energy and green economic development. Overall, the findings underscore the crucial role of the Islamic stock market in promoting sustainable economic growth and environmental sustainability in the Asia-Pacific region. The presence of minor negative effects both in the long and short term suggests the need for careful monitoring and management of stock market fluctuations to mitigate any potential adverse impacts on sustainability efforts. This study adds to the existing body of knowledge by emphasizing the importance of considering the unique dynamics of Islamic finance in the context of sustainable economic development.